2020
DOI: 10.1002/adma.202070070
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Photodetectors: Ultrahigh Responsivity Photodetectors of 2D Covalent Organic Frameworks Integrated on Graphene (Adv. Mater. 9/2020)

Abstract: In article number 1907242, Kai Xi, Peng Zhan, Fei Xu, Yanqing Lu, and co‐workers report an ultrasensitive photodetector using 2D covalent organic framework (COF)–graphene heterostructures. By selecting photoactive monomers, elaborately designed photosensitive 2D‐COFs with highly ordered donor–acceptor topologies are in situ synthesized on graphene, ultimately forming COF–graphene heterostructures. This study provides new strategies for building advanced functional devices with programmable material structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Owing to their high charge carrier mobility, AntTTH films exhibited a strong light response, even in room light, with a bias voltage of 1 V, and the on–off switching of the photocurrent can be observed many times even under very low light power in the complete UV–vis spectrum, without graphene or any other charge transporting layer (Figure f). , These properties make it a potential organic material for photodetector applications. However, with the same bias voltage, no photoresponsivity was observed for AntTTF due to the large resistance of the film.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Owing to their high charge carrier mobility, AntTTH films exhibited a strong light response, even in room light, with a bias voltage of 1 V, and the on–off switching of the photocurrent can be observed many times even under very low light power in the complete UV–vis spectrum, without graphene or any other charge transporting layer (Figure f). , These properties make it a potential organic material for photodetector applications. However, with the same bias voltage, no photoresponsivity was observed for AntTTF due to the large resistance of the film.…”
Section: Resultssupporting
confidence: 78%
“…To date, a number of semiconducting COFs have been developed carrying π-conjugated building blocks and linkers and applied in the fields of photovoltaics, , transistors, photodetectors, chemiresistive sensing, thermoelectric, and photo- and electrocatalysis. The performance of these devices strongly depends on the conductivity and intrinsic charge carrier mobility of the COFs. The charge carrier mobility of the COFs has been estimated using various contact (two/four probes, time-of-flight, hall effect, field effect transistors) and non-contact [time-resolved microwave conductivity (TRMC) and time-resolved terahertz spectroscopy] methods, and few of the π-conjugated COFs were observed to exhibit high intrinsic charge carrier mobility (∼8.1 cm 2 V –1 s –1 ), and high conductivity (∼10 –2 S cm –1 ) upon doping.…”
Section: Introductionmentioning
confidence: 99%
“…Growing crystalline COF films at confined interfaces facilitated their integration into device-relevant settings such as field-effect transistors and photodetector devices. Recently, an ultrathin 2D imine polymer film constructed from benzene-1,3,5-tricarbaldehyde and p -phenylenediamine was reported by Hu and Lei for a sandwiched nonvolatile memristor based on the filament conductive mechanism, taking advantages of the porous structure of the 2D polymer . Park et al reported the surfactant-assisted interfacial synthesis of crystalline 2D boronate ester COF films as the pseudo-gate for emulating the synaptic plasticity with a silicon nanowire field-effect transistor in a neuromorphic memory device .…”
Section: Introductionmentioning
confidence: 99%
“…These HP-COFs had relatively small bandgaps, steep onset absorption peaks, and broad spectral absorption ranging from ultraviolet to visible light, making them promising candidates for photovoltaic applications. In 2020, Xiong and his coworkers [64] synthesized hierarchically porous photosensitive 2D COFs in situ with highly ordered donor-acceptor topology on graphene by choosing photoactive tetraphenylethylene monomers. Ultimately, a HP-COF-graphene heterojunction, COF-ETBC-TAPT was successfully fabricated and used to create an ultra-sensitive optoelectronic detector.…”
Section: Optoelectronic Applicationsmentioning
confidence: 99%